NUTRITION AND HEALTH PRACTICES IN EARLY CHILDHOOD: IMPLICATION FOR CHILD DEVELOPMENT - Udeagbala, Ikechukwu R.; Ugwude, Doris I.; Bosah, Ifeoma P. (Journal of Early Childhood and Primary Education, 2020)
The study focused on the nutrition and health practices in early childhood and its implication for child development. The study was carried out in Awka South Local Government Area of Anambra State. Three research questions guided the study. Descriptive survey design was adopted to carry out the study. The population of the study was 82 private schools in Awka South L.G.A with 246 early childhood teachers. Simple random sampling was used to select 137 early childhood teachers from 52 schools randomly selected from the study area. A structured questionnaire titled Nutrition and Health Practices in Early Childhood (NHPEC) was used as the instrument for data collection which contained twenty-three (23) items. The validation of the instrument was done by three experts, two from Early Childhood and Primary Education and one expert from department of educational management and policy. Cronbach alpha was to determine the reliability of the instrument at 0.70. The analysis of the data was done through mean score. Findings revealed that, early childhood caregivers are aware in area of nutrition practices that contributes to child development but lacks programs like seminar that will help them to keep up with new knowledge that concerns nutrition and child development. And ways government is involved in issues concerning nutrition and health practices in early childcare centers is unsatisfactory. Based on the findings, it was recommended, among others, that school children should be fed with a balanced and healthy diet and regular scheduled immunization should be maintained by the government.